Effect of a fluoride-releasing fissure sealant and a conventional fissure sealant on inhibition of primary carious lesions with or without exposure to fluoride-containing toothpaste - Zahra Khalili sadrabad; Ebrahim Safari; Maryam Alavi; Mohammad Mostafa Shadkar; Seyed Hamid Hosseini Naghavi (Tabriz University of Medical Sciences, 2019)
Background. Fluoride-releasing capacity has been added to fissure sealants to benefit from the positive anticariogenic effects of both sealants and fluoride. This comparative research investigated the inhibitory effects of conventional and fluoridereleasing fissure sealants on initial lesions with or without exposure to fluoride toothpaste. Methods. Cavities were prepared on buccal surfaces of 24 premolar teeth which were randomly divided into three groups. In the cavities of the first group, a fluoride-releasing fissure sealant and in the second group, a conventional fissure sealant were placed; the third group was left intact. Incipient lesions were produced around the cavities. Each group was divided into two subgroups, which were exposed to fluoride-containing toothpaste or artificial saliva. Lesion depths were measured under a polarized light microscope before and after treatment. Changes in lesion depths in the samples were analyzed by SPSS 17. Results. Initial and final caries depths were significantly lower in the fluoride-releasing fissure sealant group compared to the other groups (P<0.001). The average depths of carious lesions were lower in subgroups exposed to fluoride-containing toothpaste than the subgroups exposed to artificial saliva and the difference was significant in the conventional sealant group and the group without sealant (P<0.001); however, the difference between the toothpaste-exposed and saliva-exposed subgroups was not significant in the fluoride-releasing fissure sealant group (P=0.721). Conclusion. Incorporation of fluoride into the fissure sealants can be effective in the inhibition of dental caries. It seems that fluoride, released from fluoride-releasing sealants, overwhelms the remineralizing capacity of fluoride released from the toothpaste on the same tooth.